Travel-induced circadian and microbiota disturbances: implications for athlete health and performance: a narrative review - Bilinski, K.; Wisniewski, K.; Rafner, L.; Witko, P.; Gawel-Dabrowska, D. (Nutrients, 2026)
High-performance athletes are increasingly exposed to frequent trans-meridian travel, leading to profound circadian desynchronization and gastrointestinal distress. This review examines the complex interplay between the host`s central circadian system and the gut microbiota (GM), both of which exhibit synchronised daily oscillations essential for homeostasis. Rapid time-zone transitions, such as those anticipated for the 2026 FIFA World Cup, induce a state of "gut jet lag," characterised by the loss of rhythmic microbial functions and impaired intestinal barrier integrity. Circadian misalignment is associated with increased systemic inflammation and disrupted metabolic regulation, which may contribute to impairments in cognitive performance, sleep quality, and muscle recovery. Critically, travel-induced dysbiosis may reduce the production of microbial metabolites, specifically short-chain fatty acids (SCFAs) like acetate, propionate, and butyrate. These SCFAs serve as energy substrates that may enhance glucose uptake, lipid oxidation, and glycogen storage in skeletal muscle. Evidence suggests that travel-related stressors—including dehydration, psychological stress, and shifts toward highly processed diets—further exacerbate the loss of beneficial taxa. To mitigate these effects, this article proposes evidence-informed strategies: timed light exposure to reset the master clock, chronobiotic meal timing to entrain peripheral tissues, and targeted symbiotic supplementation to restore SCFA-producing populations. Integrating these personalised, evidence-informed protocols may support the optimisation of physiological resilience and performance.